Perception of The Students on Speaking Practice in English Club Activities at MA DDI Kanang - Alwiah, Artati; Abduh, Amirullah; Munir, Munir (Program Studi Pendidikan Bahasa Inggris FBS UNM, 2023)
The purpose of this study is to ascertain if students view speaking practice in English club activities as beneficial or detrimental. To accomplish its research goals, this study employed qualitative methodologies. Ten students who joined the English club were the study's participants. The random sampling technique was employed to pick the participants. Interviews and documentation are the research instruments used in this study. The study's findings demonstrate that students can greatly benefit from attending English clubs to improve their speaking. The students received more positive perceptions than negative perceptions. For positive perceptions, the benefits felt by students are that they can speak English, are more confident when speaking in public using English, their self-confidence trained in English club, register new vocabulary and gaining new friends. Students are also motivated to join English clubs because they can learn more about English, learning more fun, and they want to go abroad and communicate with foreigners easily. Then, for the negative perceptions of some students, the obstacles or difficulties experienced are lack of time exposure and pronunciation that is still convoluted. The challenges faced by English club activities are lack of funds. Although English club members experience obstacles and difficulties, they still have the desire or intention to continue learning English, where they feel there are more advantages than disadvantages.